2003
DOI: 10.1021/ol0352714
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Keto-Enamine Salicylideneanilines

Abstract: [reaction: see text] Highly stable NH salicylideneanilines have been prepared by reaction of 1,3,5-triformylphloroglucinol with aniline derivatives. The NH form was confirmed by X-ray crystallographic data, as well as by NMR studies. A convenient one-step synthesis of triformylphloroglucinol is also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
203
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(219 citation statements)
references
References 36 publications
12
203
0
1
Order By: Relevance
“…The generation of a keto-enamine species has been previously observed in similar cases and confirmed through X-ray diffraction, being attributed to the relatively higher basicity of the nitrogen against that of the phenolic oxygen. 21 The comparison of the traditionally admitted and the newly proposed TSs, revealed that in the accepted approximation the C-C bond being formed has smaller distances (1.81-1.87 Å) and smaller Wiberg bond indexes (WBI, 0.56-0.59) than in this newly discovered attack mode (Fig. 1).…”
Section: Resultsmentioning
confidence: 87%
“…The generation of a keto-enamine species has been previously observed in similar cases and confirmed through X-ray diffraction, being attributed to the relatively higher basicity of the nitrogen against that of the phenolic oxygen. 21 The comparison of the traditionally admitted and the newly proposed TSs, revealed that in the accepted approximation the C-C bond being formed has smaller distances (1.81-1.87 Å) and smaller Wiberg bond indexes (WBI, 0.56-0.59) than in this newly discovered attack mode (Fig. 1).…”
Section: Resultsmentioning
confidence: 87%
“…2,4,6-Triformylphloroglucinol (H 3 11) [30] and 2,4,6-triacetylphloroglucinol (H 3 12) [133] were prepared according to reported procedures. The assignments of the NMR resonances (Scheme 7) in all products were supported by 2D COSY, HMBC, and HMQC spectroscopy.…”
Section: Methodsmentioning
confidence: 99%
“…This high stability arises from the irreversible nature of the imine-to-enamine tautomeric step, which is attributable to the reasonably large basicity of the -NH group and then the phenolic -OH group, leading to a stable β-ketoenamine linkage. 30 …”
Section: Introductionmentioning
confidence: 99%